PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DALAM PEMBELAJARAN IPS SISWA KELAS IV SD NEGERI NAWANGSASI - Krisma Dwi Sagita; Elya Rosalina; Andri Valen (Primary Education Journal Silampari (PEJS), 2022)
This study aims to determine the completeness of social studies learning outcomes for fourth grade students of SD Negeri Nawangsasi for the 2020/2021 academic year after the application of the Cooperative Script learning model. The method used in this research is an experimental method with a pre-experimental research design. The population in this study were all fourth grade students of SD Negeri Nawangsasi and the sample in this study amounted to 28 students who were determined by saturated sampling. The data collected were analyzed using the z-test at the significant level α = 0.05, the zcount was 2.52 and> ztable was (1.64), so it could be concluded that the social studies learning outcomes of the fourth grade students of SD Negeri Nawangsasi used the Cooperative Script learning model. significantly complete. Keywords: Cooperative Script Model, Social Studies Learning, Learning Outcomes, Elementary School